Patenting nature or protecting culture? Ethnopharmacology and indigenous intellectual property rights - McGonigle, Ian Vincent (J Law Biosci, 2016)
Ethnopharmacologists are scientists and anthropologists that study indigenous medicines and healing practices, and who often develop new therapies and medicines for wider use. Ethnopharmacologists do fieldwork with indigenous peoples in traditional societies, where they encounter a wide range of cultural values and varying ideas about the nature of property relations. This poses difficulties for protecting indigenous intellectual property and for making just trade agreements. This Note reviews the legal issues relevant to the protection of indigenous resources in ethnopharmacology trade agreements, and suggests that recent developments in anthropology and the social study of science could be instructive in furthering the legal discourse and in providing policy directions. Specifically, the Note introduces the concepts of ‘ontological pluralism’ and ‘epistemic subsidiarity’, which could help lawmakers write sui generis trade agreements to better protect indigenous knowledge and resources.